Antibacterial Effectiveness of Rambutan Peel Extract (Nephelium lappaceum L.) in Inhibiting the Growth of Enterococcus Faecalis Bacteria - Wijaya, Cindy Denhara; Rajindervir Singh; Mellisa Sim (HM Publisher, 2022)
Backgrounds. This research is a study that seeks to explore the potential of rambutan extract in inhibiting the growth of Enterococcus faecalis bacteria, where this bacterium is one of the bacteria that is often found in the oral cavity and often causes infections and dental and oral problems. Methods. This research is an experimental study in vitro. This study aims to determine the diameter of the inhibition zone of rambutan peel extract on Enterococcus faecalis. Rambutan peel extracts were tested at levels of 5%, 7.5% and 10% with NaOCl (Sodium Hypochlorite) 2.5% control, where each test group was tested on 6 culture plates of Enterococcus faecalis bacteria. Results. The 10% rambutan peel extract group had the highest inhibition zone diameter of 12.4 ± 1.21 mm. Rambutan peel extract 5% - 10% showed a higher inhibition zone diameter than the control NaOCl 2.5%. The results of the effectiveness test of the diameter of the inhibition zone between the test groups. Rambutan peel extracts 5%, 7.5% and 10% showed different levels of inhibition zone diameter compared to 2.5% NaOCl. Rambutan peel extract 5%, 7.5%, and 10% had a higher diameter of the inhibition zone than the 2.5% NaOCl control. Conclusion. Rambutan peel extract 5%, 7.5% and 10% were more effective in inhibiting the growth of Enterococcus faecalis than control NaOCl.